Combination of cellulose nanofiber and artificial fusion protein for biocementation - Nawarathna, Thiloththama Hiranya Kumari; Sakai, Jin; Nakashima, Kazunori; Kawabe, Tetsuya; Shikama, Miki; Takano, Chikara; Kawasaki, Satoru (Frontiers in Built Environment, 2024)
Biomineralization occurring in living organisms is mostly controlled by organic macromolecules such as polysaccharides and proteins. Recently, biomineralization is attracting much attention as a green and sustainable cementation technique including enzyme-induced carbonate precipitation (EICP), where CaCO3 is formed by hydrolysis of urea by urease in the presence of calcium ion. In this study, we have developed a novel hybrid biocementation method combining CaCO3 and cellulose nanofiber (CNF). In nature, matrix proteins work as a binder at the interface of organic and inorganic materials to form hybrid bio-materials. By mimicking the natural system, we designed artificial fusion protein to facilitate the deposition of CaCO3 on CNF. Calcite-binding peptide (CaBP) and carbohydrate binding module (CBM) were introduced in the artificial fusion protein CaBP-CBM to connect CaCO3 and cellulose. The addition of CNF in EICP system resulted in the formation of a number of small particles of CaCO3 compared to non-additive system. The addition of the fusion protein CaBP-CBM to CNF led to the increase in the size of CaCO3 particles. Furthermore, the combination of CaBP-CBM and CNF provides the higher strength of samples in sand solidification. Therefore, introduction of CNF and fusion protein would be promising for novel biocementation techniques.